MON-724 Crude Protein Extract of Pyropia Yezoensis Protects Against Tumor Necrosis Factor-á-Induced Apoptosis and Atrophy in C2C12 Myotubes - Lee, Min-Kyeong (J Endocr Soc, 2020)
Proinflammatory cytokines such as tumor necrosis factor (TNF)-α play an important role in the development of skeletal muscle atrophy, and TNF-α-induced apoptosis may mediate skeletal muscle atrophy. Therefore, we evaluated the effect of Pyropia yezoensis crude protein (PYCP) on TNF-α-induced apoptosis and identified the involved signaling pathways. For this purpose, C2C12 myotubes were treated with 20 ng/mL TNF-α in the presence or absence of 25-100 μg/mL PYCP for 48 h. Treatment with TNF-α markedly increased the protein level of TNF-receptor 1 (TNF-R1). In contrast, treatment with PYCP downregulated the TNF-α-induced increase in the TNF-R1 protein level. Also, the expression of Bax, Bcl-2, cytochrome C, and apoptosis-inducing factor, markers of apoptosis in myofibers, was increased by TNF-α, but this effect was inhibited by PYCP in a concentration-dependent manner. In addition, exposure of C2C12 myotubes to TNF-α for 48 h enhanced the activity of caspase-3, which was significantly inhibited by PYCP. Furthermore, poly[ADP-ribose] polymerase cleavage and histone-associated DNA fragmentation were markedly increased by TNF-α and attenuated by PYCP in a concentration-dependent manner. In conclusion, the ability of PYCP to inhibit the apoptosis induced by TNF-α suggests that it has therapeutic potential for skeletal muscle atrophy.